"It just happens". Care home residents' experiences and expectations of accessing GP care. (November 2018) - Victor, Christina; Davies, Susan; Dickinson, Angela; Morbey, Hazel; Masey, Helen; Gage, Heather; Froggatt, Katherine; Iliffe, Steve; Goodman, Claire
Highlights: Older people in care homes had low expectations of their health status Care home residents had low expectations of the ability of health services to address their health problems. Residents predominantly used intermediaries (staff or family) to access health care. Residents anticipated that staff would proactively initiate health care access. Abstract: Background: Care homes provide personal care and support for older people who can no longer be supported in the community. As part of a larger study of integrated working between the NHS and care homes we asked older people how they accessed health care services. Our aim was to understand how older people resident in care homes access health services using the Andersen model of health care access. Methods: Case studies were conducted in six care homes with different socio-economic characteristics, size and ownership in three study sites. Residents in all care homes with capacity to participate were eligible for the study. Interviews explored how residents accessed NHS professionals. The Andersen model of health seeking behaviour was our analytic framework. Findings: Thirty-five participants were interviewed with an average of 4 different conditions. Expectations of their health and the effectiveness of services to mitigate their problems were low. Enabling factors were the use of intermediaries (usually staff, but also relatives) to seek access. Residents expected that care home staff would monitor changes in their health and seek appropriate help unprompted. Conclusions: Care home residents may normalise their health care needs and frame services as unable to remediate these which may combine to disincline older care home residents to seek care. Care access was enabled using intermediaries -either staff or relatives-and the expectation that staff would proactively seek care when they observed new/changed needs. Residents may over-estimate the health-related knowledge of care home staff and their ability to initiate referrals to NHS professionals.